2020
DOI: 10.7150/thno.46123
|View full text |Cite
|
Sign up to set email alerts
|

Improved cardiovascular risk prediction in patients with end-stage renal disease on hemodialysis using machine learning modeling and circulating microribonucleic acids

Abstract: Rationale: To test whether novel biomarkers, such as microribonucleic acids (miRNAs), and nonstandard predictive models, such as decision tree learning, provide useful information for medical decision-making in patients on hemodialysis (HD). Methods: Samples from patients with end-stage renal disease receiving HD included in the AURORA trial were investigated (n=810). The study included two independent phases: phase I (matched cases and controls, n=410) and phase II (unmatche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 53 publications
0
22
0
Order By: Relevance
“…Simultaneous assessment of miRNA profiles or miRNA ratios may hold promise to provide more comprehensive information about the clinical evolution of the patient. This hypothesis, which seems to be true for circulating miRNAs (34), can also be translated to respiratory specimens such as BAS. Using multivariable analysis for multimarker analysis, we constructed a miRNA ratio-based prediction model (miRNA ratio score) to optimize the best combination of ratios for risk prediction.…”
Section: Clinical Implications For the Management Of Critically Ill P...mentioning
confidence: 83%
“…Simultaneous assessment of miRNA profiles or miRNA ratios may hold promise to provide more comprehensive information about the clinical evolution of the patient. This hypothesis, which seems to be true for circulating miRNAs (34), can also be translated to respiratory specimens such as BAS. Using multivariable analysis for multimarker analysis, we constructed a miRNA ratio-based prediction model (miRNA ratio score) to optimize the best combination of ratios for risk prediction.…”
Section: Clinical Implications For the Management Of Critically Ill P...mentioning
confidence: 83%
“…The ideal scenario for miRNA testing seems to be based on the concept of "several miRNAs-one disease", contrary to the traditional "one miRNA-one disease" concept. 12 Therefore, we explored whether COVID-19 severity could be associated with a specific miRNA signature. Multivariate predictive models were constructed using a variable selection process based on LASSO regression.…”
Section: Impact Of Covid-19 Severity On the Circulating Microrna Profilementioning
confidence: 99%
“…10 The results suggest that miRNAs are sensitive, robust and cost-effective biomarkers that offer additional information to clinical variables and already established clinical indicators. 11,12 Indeed, several miRNA-based diagnostic products are already available for clinical practice. 13 Here, we aimed to examine the circulating miRNA profile of hospitalized COVID-19 patients and explore the potential role and clinical significance as biomarkers of disease severity.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Alvin et al pointed out that the predictive model based on machine learning could reliably identify patients who have high-risk diseases and increase the utilization of healthcare services ( Rajkomar et al, 2019 ). David et al used machine learning algorithms to improve the cardiovascular risk prediction of patients with end-stage renal disease on hemodialysis ( de Gonzalo-Calvo et al, 2020 ). Michalis et al also found that, based on machine learning algorithms, using volatile organic compounds in exhaled gas as predictors distinguishes lung cancer from other lung diseases or healthy individuals well ( Zhang Z. et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the LG-based approach fails to consider the complex non-linear interactions between variables, which can be captured by more sophisticated model algorithms, thus improving the accuracy of risk prediction. Recently, machine learning has been widely applied to the development of clinical tools for disease diagnosis ( Rajkomar et al, 2019 ; de Gonzalo-Calvo et al, 2020 ; Zhang Z. et al, 2021 ). Unlike the traditional LG-based approach, machine learning can recognize hidden patterns and non-linear interactions in complex data, allowing for a better assessment of clinical outcomes ( Myszczynska et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%